مساهمة العلاقات العامة الإلكترونية في تحسين الصورة الذهنية للمؤسسة دراسة ميدانية على عينة زبائن اتصالات الجزائر-سوق اهراس - صياد سارة; رحال أمل (My University, 2022)
ABSTRACT This study aims to recognize the contribution of electronic public relations to improving the mental image of the institution, where electronic public relations came to create new systems and methods of work to achieve wealth and added value, the latter based on innovation and innovation. The study, which was conducted on the clients of The Algiers-Souq Ehras Communications Corporation, aims to uncover the most important electronic means used on electronic business relationships to communicate with ts audience, in an attempt to find out the public opinions about the performance of electronic public relations in the institution. In our study, we relied on the descriptive approach, because it is suitable for this type of research, and as for the sample of the study we chose the intended sample and this to answer the main question of this study. This study is one of the studies that deals with the use of electronic technology in public relations on future studies. --------------------------------------- ملخص تهدف هذه الدراسة إلى التعرف على مساهمة العلاقات العامة الإلكترونية في تحسين الصورة الذهنية للمؤسسة، حيث جاءت العلاقات العامة الإلكترونية لابتكار أنظمة وأساليب عمل جديدة لتحقيق الثراء والقيمة المضافة، قائمة على الابتكار والإبداع. تهدف الدراسة، التي أجريت على عملاء مؤسسة الجزائر سوق أهراس للاتصالات، إلى الكشف عن أهم الوسائل الإلكترونية المستخدمة في علاقات العمل الإلكترونية للتواصل مع جمهورها، في محاولة لمعرفة آراء الجمهور حول أداء العلاقات العامة الإلكترونية في المؤسسة. اعتمدنا في دراستنا على المنهج الوصفي، لملاءمته لهذا النوع من الأبحاث، أما بالنسبة لعينة الدراسة، فقد اخترنا العينة المستهدفة، وذلك للإجابة على التساؤل الرئيسي لهذه الدراسة. تُعد هذه الدراسة من الدراسات التي تتناول استخدام التكنولوجيا الإلكترونية في العلاقات العامة ضمن الدراسات المستقبلية.
Keywords: العلاقات العامة الإلكترونية